2009
DOI: 10.1021/cg801019d
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystal Formation in Solution: In Situ Solute Concentration Monitoring of the Two Components and Kinetic Pathways

Abstract: The purpose of this work was to investigate the kinetic pathways in the phase solubility diagram of a cocrystallization process in solution. A cocrystal model composed of an active pharmaceutical ingredient (carbamazepine, CBZ) and a vitamin (nicotinamide, NCT) was selected. Batch experiments were performed in a stirred vessel. The process monitoring was carried out using in situ ATR-FTIR spectroscopy, which provided estimates of the solute concentrations of both CBZ and NCT at different temperatures. In the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 18 publications
1
65
0
Order By: Relevance
“…92) Some approaches have reduced inorganic solvent use during cocrystal production. Specifically, carbon dioxide gas addition effectively induces itraconazolesuccinic acid cocrystal formation and precipitation from aqueous solution (e.g., gas antisolvent (GAS) method).…”
Section: Manufacturing Of Cocrystalsmentioning
confidence: 99%
“…92) Some approaches have reduced inorganic solvent use during cocrystal production. Specifically, carbon dioxide gas addition effectively induces itraconazolesuccinic acid cocrystal formation and precipitation from aqueous solution (e.g., gas antisolvent (GAS) method).…”
Section: Manufacturing Of Cocrystalsmentioning
confidence: 99%
“…However, many of the current methods used to isolate co-crystal forms such as neat and liquid assisted grinding [10], [11], slurry conversion [12], [13], supercritical fluid enhanced atomization [14], and evaporative co-crystallization [13], [15], [16] cannot be scaled to industrial production capacity. Cooling crystallization is perhaps the most viable route to scale-up, yet there are only a few studies that have explored this method to isolate co-crystals [17]- [19]. There are even fewer studies that are carried out using large scale laboratory crystallizers (that is, 500 -1L capacity) [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Cooling crystallization is perhaps the most viable route to scale-up, yet there are only a few studies that have explored this method to isolate co-crystals [17]- [19]. There are even fewer studies that are carried out using large scale laboratory crystallizers (that is, 500 -1L capacity) [17], [18]. In addition, there is limited use of process analytical technologies (PAT) to monitor, control and characterize cocrystallization processes [16], [18].…”
Section: Introductionmentioning
confidence: 99%
“…ATR-FTIR spectroscopy can be used to identify the concentrations of the two co-crystal forming substances independently. In the case of carbamazepine and nicotinamide, it was found that the formation of the co-crystals of carbamazepine/nicotinamide (1 : 1) is in competition with the formation of pure carbamazepine crystals (Gagniere et al, 2009). Since the stoichiometric ratio of the co-crystal is known, the formation of co-crystals should change the concentrations of the two compounds in that ratio.…”
Section: Co-crystal Formationmentioning
confidence: 99%